(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
This article investigates peculiarities of using flower images in the poetic writing of Mykola Kondratovych Voronyi, who is one of the most prominent representatives of early Ukrainian modernism, especially symbolism and aestheticism. This paper determines the leading features of the content, functional and stylistic meaning in the corresponding symbolic images represented in the lyric poetry of M. Voronyi. It also emphasizes the ambivalence of using the analyzed images in the poetic discourse of the author.